Can an immune-regulatory vaccine prevent HIV infection?. Issue 3 (March 2012) - Boettler, Tobias; Cunha-Neto, Edecio; Kalil, Jorge; von Herrath, Matthias
Developing vaccines to prevent the establishment of HIV infection has been fraught with difficulties. It might therefore be important to consider other new strategies. Since several studies suggest that anti-inflammatory stimuli can protect from HIV infection and because HIV replicates preferably in activated T cells, we suggest here that the reduction of immune activation through a HIV-specific regulatory T-cell vaccine might thwart early viral replication. Thus, because immune activation is a good predictor of disease progression and the immune activation set point has been shown to be an early event during HIV infection, vaccinating to achieve control of early virus-specific immune activation might be advantageous.